Listening effort: Are we measuring cognition or affect, or both? - Francis, Alexander L; Love, Jordan (Wiley interdisciplinary reviews. Cognitive science, 2020)
Listening effort is increasingly recognized as a factor in communication, particularly for and with nonnative speakers, for the elderly, for individuals with hearing impairment and/or for those working in noise. However, as highlighted by McGarrigle et al., International Journal of Audiology, 2014, 53, 433-445, the term "listening effort" encompasses a wide variety of concepts, including the engagement and control of multiple possibly distinct neural systems for information processing, and the affective response to the expenditure of those resources in a given context. Thus, experimental or clinical methods intended to objectively quantify listening effort may ultimately reflect a complex interaction between the operations of one or more of those information processing systems, and/or the affective and motivational response to the demand on those systems. Here we examine theoretical, behavioral, and psychophysiological factors related to resolving the question of what we are measuring, and why, when we measure "listening effort." This article is categorized under: Linguistics > Language in Mind and Brain Psychology > Theory and Methods Psychology > Attention Psychology > Emotion and Motivation.